The Political Economy of Crime: did Universal Credit Increase Crime Rates? - Tiratelli, Matteo (The British journal of criminology, 2023)
Interest in the political economy of crime goes back to sociology’s founding fathers, but the nature of the relationship between restrictive social security systems and crime remains contested. This paper exploits exogenous variation in the introduction of Universal Credit (UC) to local areas across England and Wales to address this question. We first use fixed effects models, with a range of controls, to show that as UC enrolments increase in a given area, so does the crime rate. We then use interrupted time series analysis to show that, despite UC being rolled out at different times in different places, its introduction in each local area coincides with a positive shift in the trend in crime. These findings hold for total crime, property crime and violent crime. Borrowing from Strain Theory and Routine Activities Theory, we suggest that changes to the pool of motivated offenders may help to explain these correlations.